Associations of working from home with occupational physical activity and sedentary behavior under the COVID‐19 pandemic. Issue 1 (8th March 2021) - Fukushima, Noritoshi; Machida, Masaki; Kikuchi, Hiroyuki; Amagasa, Shiho; Hayashi, Toshio; Odagiri, Yuko; Takamiya, Tomoko; Inoue, Shigeru
Abstract: Objectives: To compare physical activity (PA) and sedentary behavior (SB) levels during work time between those who work from home (WFH) and at workplaces (no WFH), and by WFH subgroups. Methods: This cross‐sectional internet‐based survey included 1239 workers (mean age [standard deviation], 44.7 [13.7] years; 59.2% men) living in the Tokyo Metropolitan Area. Time spent sitting (SB), standing (light‐intensity PA; LPA), walking, and engaging in heavy labor (moderate‐to‐vigorous PA; MVPA) during work time was measured using the Work‐related Physical Activity Questionnaire. Workers reported weekly WFH percentages (eg, 0% implies no WFH and 100% implies full WFH), and WFH percentages were categorized into no WFH (0% WFH) and WFH (1%‐100% WFH) groups. The WFH group was further subcategorized into 1%‐25%, 26%‐50%, 51%‐75%, and 76%‐100% subgroups. Results: Overall, 494 workers (39.9%) worked from home. During working hours, SB time was longer in the WFH group than in the no WFH group (mean minutes [% working‐time SB]: 335.7 vs 224.7 min [74% vs 50%]). Significantly shorter LPA and MVPA times (%) were reported in the WFH group than in the no WFH group (LPA, 59.6 vs 122.9 min [14% vs 29%]; MVPA, 55.3 vs 91.9 min [13% vs 22%], all P  < .001). Among the WFH subgroups, longer SB time and shorter LPA and MVPA times were observed in the highest WFH group (WFH 76%‐100%) than in the WFH 1%‐25% and 26%‐50% subgroups. Conclusions: Workers who telecommuted were less physically active and had longer sedentary during work time than those who worked at the workplaces.